REPRESENTAÇÃO DAS ELEIÇÕES EM NAZARÉ/TO E AS ELEIÇÕES DE 2016 - Mouzinho, Tania Araújo (Universidade Federal do Tocantins, 2022)
This work has as main objective to reconstruct the scenario of the municipal elections of Nazaré / To, in the year 2016, thus highlighting the political functions attributed to the councilmen and effectiveness of their position. For the development of this work, a qualitative research was carried out, through the historical reconstruction of the last municipal election, as well as empirical data from the TRE and TSE, which were fundamental for the results found, we also carried out a questionnaire for the interview with the councilmen.